Rancang bangun sistem informasi penerbitan dokumen kependudukan berbasis website - Saryani, Saryani; Libriantono, Bambang; Kusumah, Ferdina (Universitas Tangerang Raya, 2022)
Processing population data in Gandasari Village is currently still limited to the use of Microsoft Excel for reporting and data input purposes. However, there is no special system that can manage population data comprehensively. This research aims to overcome these shortcomings by designing and implementing an effective system for managing population data. Data collection methods were carried out through observation, literature study, and interviews with sub-district staff. The program developed uses the PHP programming language and MySQL database. The system testing process uses Black Box Testing to ensure optimal performance. SWOT and Elicitation analysis are used to analyze strengths, weaknesses, opportunities and threats in system development. This research focuses on developing a system for issuing documents, such as domicile certificates, birth certificates, death certificates and marriage certificates. It is hoped that the implementation of this new system will increase efficiency in managing population data, reduce document processing time, and increase community satisfaction in getting fast and accurate administrative services from Gandasari Village. Keywords: Management, SWOT, Website